ANALISIS STRATEGI PEMASARAN DALAM KEPUASAN PELANGGAN DI PT BORWITA CITRA PRIMA - Azzah Arrafi; Indrawati Yuhertiana (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to analyze the marketing strategies implemented by PT Borwita Citra Prima in attracting and retaining customers. The research method used is qualitative descriptive analysis research, which integrates data from literature, customer surveys, and interviews with company management. The concept of consumer satisfaction is the main focus, describing how satisfaction affects customer loyalty in long-term relationships. Borwita Citra Prima, through developing innovative and customer-oriented marketing strategies, has expanded its business from distribution of consumer products to logistics services. Marketing strategy analysis highlights the importance of using the right marketing mix, such as product, price, promotion, and distribution, to meet target market needs. A customer-focused marketing approach is key in maintaining Borwita Citra Prima's position as a leader in the distribution industry, facing dynamic market challenges.